2013
DOI: 10.1007/s10482-013-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein association and cellular localization of four essential gene products encoded by tellurite resistance-conferring cluster “ter” from pathogenic Escherichia coli

Abstract: Gene cluster "ter" conferring high tellurite resistance has been identified in various pathogenic bacteria including Escherichia coli O157:H7. However, the precise mechanism as well as the molecular function of the respective gene products is unclear. Here we describe protein-protein association and localization analyses of four essential Ter proteins encoded by minimal resistance-conferring fragment (terBCDE) by means of recombinant expression. By using a two-plasmid complementation system we show that the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Protein TerD and TerE form strong heterodimeric complexes. Further, protein localization analyzes indicate that TerC may serve as a membrane protein and on its cytoplasmic side interacts with TerB and TerE, and the latter of these proteins further associates with TerD present in the cytoplasm [ 41 ]. These findings support the speculation that the Ter proteins are involved in as yet uncharacterized bacterial stress recognizing mechanism operating during infection processes.…”
Section: Discussionmentioning
confidence: 99%
“…Protein TerD and TerE form strong heterodimeric complexes. Further, protein localization analyzes indicate that TerC may serve as a membrane protein and on its cytoplasmic side interacts with TerB and TerE, and the latter of these proteins further associates with TerD present in the cytoplasm [ 41 ]. These findings support the speculation that the Ter proteins are involved in as yet uncharacterized bacterial stress recognizing mechanism operating during infection processes.…”
Section: Discussionmentioning
confidence: 99%
“…The elements can be chromosomally encoded as well, such as tehAB from E. coli [96], trgABcysK and telA from R. sphaeroides [134], and the tmp gene from Pseudomonas syringae [135]. However, the molecular basis behind most of these systems is unclear [136]. Other strategies are employed for resistance; however, they do not involve direct enzymatic reduction.…”
Section: Aerobic Resistancementioning
confidence: 99%
“…It does confer high-level resistance (minimum inhibitory concentration (MIC) of 1028 µ g/mL), but the details are still under study. Work with the minimal resistance-conferring fragment (terBCDE) has shown that resistance can only be achieved by the expression of all four components [136]. In this case, they each play an irreplaceable role, likely involving their mutual association at the inner membrane [136].…”
Section: Ter Operonmentioning
confidence: 99%
See 2 more Smart Citations